A comparative assessment of plant flammability through a functional approach: The case of woody species from Argentine Chaco region. (28th August 2019) - Santacruz‐García, Ana Carolina; Bravo, Sandra; del Corro, Florencia; Ojeda, Fernando
Abstract: Recent changes to fire regimes in many regions of the world have led to renewed interest in plant flammability experiments to understand and predict the consequences of such changes. These experiments require the development of practical and standardised flammability testing protocols. The research aims were (i) to compare plant flammability assessments carried out using two different approaches, namely functional trait analysis and testing with a shoot‐level device; and (ii) to evaluate the effect of disturbances and seasonal variability on flammability. The study area was located in the Western Chaco region, Argentina, and 11 species were selected based on their representativeness in forests. We studied six functional traits related to flammability, growth habit and foliar persistence, in forests without disturbances over the three last decades as well as in disturbed forests. The seasonal variation of these functional traits was evaluated over two consecutive years. Functional trait flammability index (FI) and shoot‐level measurements followed standard protocols. Sixty per cent of the species measured presented a high to very high FI. The results of both assessment methods were significantly correlated. Both methods identified the same species as having medium flammability, but differed in regards to the most flammable species. Senegalia gilliesii was identified as the most flammable species when using functional trait analysis, whereas shoot‐level assessments found Larrea divaricata and Schinus johnstonii to be the most flammable. There were no disturbance effects on the FI but there was seasonal variation. Our results validate the use of functional traits as a predictive method of flammability testing and represent the first global effort comparing flammability obtained through functional trait analysis with empirical measurements. The significant correlation between both methods allows the selection of the one that is more appropriate for the size of the area to be evaluated and for the availability of technical resources. Abstract in Spanish is available with online material. Resumen: Cambios recientes en los regímenes de fuego a nivel mundial han aumentado el interés en los experimentos de inflamabilidad vegetal. Estos experimentos requieren el desarrollo de protocolos prácticos y estandarizados. El presente trabajo comparó dos metodologías para determinar la inflamabilidad: rasgos funcionales (RF) y pruebas con un dispositivo de baja tecnología (DBT); y evaluó el efecto de los disturbios y la estacionalidad en la inflamabilidad. Los experimentos se realizaron en la Región Chaqueña Occidental, Argentina, y once especies fueron seleccionadas según su representatividad. Se evaluaron seis RF relacionados con la inflamabilidad, el hábito de crecimiento y la persistencia foliar, en bosques sin disturbios (desde hace 30 años), así como en bosques disturbados. Se evaluó la variación estacional de estos RF durante dos años consecutivos. El índice de inflamabilidad (IF) obtenido a través de RF y las mediciones a través del dispositivo de baja tecnología siguieron protocolos estándarizados. El 60 % de las especies evaluadas presentó un IF alto a muy alto. Hubo una correlación significativa entre los dos métodos de determinación de inflamabilidad. Ambos métodos identificaron las mismas especies en el grupo de inflamabilidad media; sin embargo, hubo diferencias en cuanto a las especies más inflamables. A través del análisis de RF, Senegalia gilliesii fue la especie con mayor inflamabilidad, mientras que a través del DBT, Larrea divaricata y Schinus johnstonii tuvieron mayor inflamabilidad. No hubo efecto de los disturbios en el IF, pero sí hubo variación estacional. Nuestros resultados validan el uso de rasgos funcionales como un método predictivo de la inflamabilidad vegetal y representan el primer esfuerzo global para comparar la inflamabilidad obtenida a través del análisis de rasgos funcionales con mediciones empíricas. La correlación significativa entre ambos métodos permite seleccionar el método más apropiado según el tamaño del área a evaluar y la disponibilidad de recursos técnicos.